TRANSFORMASI SOSIAL PADA UPACARA RAMBU SOLO DIRAPAI DI RANTEPAO TORAJA UTARA - rahleda rahleda (Jurnal Sosiologi Agama, 2016)
This study examines the shift rambu solo dirapai ceremony in conjunction with the social changes that occurred in the Toraja people. This study covers the forms of commodification is happening in the ceremony, interpendensi and social relations, as well as forms of figuration and habitus as a supporting component of a shift in the ceremony rambu solo dirapai. In this paper illustrates that ritual rambu solo dirapai shifting meanings and social values in society, first carried out in order to customary funeral procession of bodies of the nobility, now used as a means to obtain the existence in society and have also been used as a commodity for the benefit of tourism, so the ceremony rambu solo dirapai who had now become profane sacred nature. At the local elite also changes the structure, which was once the relationship is between traditional leaders and communities are now going a new power relationship that is influenced by the government as the new power relations by making ceremony rambu solo dirapai as tourism attraction in Toraja. In the shift between traditional leaders and the government as the new power relations created a balanced power relationship so there is no contradiction in the ceremony rambu solo dirapai as indigenous and as a tourism commodity. Keywords: Ceremony Rambu Solo Dirapai, Social Transformation, Figuration